Effect of milled electrical cable waste on mechanical properties of concrete - Grinys, Audrius; Vaičiukynienė, Danutė; Augonis, Algirdas; Sivilevičius, Henrikas; Bistrickait, Rėda (Journal of Civil Engineering and Management, 2015)
The article focuses on investigation of mechanical and fracture properties of concrete containing electrical cable waste as well as some microstructural features of such concrete. Added to concrete, electrical cable waste reduces the overall concrete bulk density. Compressive, flexural, tensile splitting strengths and elastic modulus decreased when electrical cable waste was admixed to conventional and polymer modified concretes. The best mechanical properties of concrete samples containing electrical cable waste were identified in polymer modified concrete containing 5% of electrical cable waste. Electrical cable waste particles increase the deformability of polymer modified concretes and have almost no influence on normal concrete. Consequently, the optimal amount of electrical cable waste particles can provide concrete with desirable strength that is required for different applications.